2013
DOI: 10.1021/jo3027033
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Phenanthridine Derivatives by Microwave-Mediated Cyclization of o-Furyl(allylamino)arenes

Abstract: A novel and efficient synthesis of phenanthridines and aza analogues is reported. The key step is a microwave-mediated intramolecular Diels-Alder cyclization of o-furyl(allylamino)arenes. In the presence of a catalytic amount of acid, the DA-adduct reacts further to give the dihydrophenanthridines, which easily can be oxidized to fully aromatic compounds by air in the presence of UV light or by DDQ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 27 publications
1
27
0
1
Order By: Relevance
“…No formation of alcohol 4b or ketone 5b was observed. It is worth noting that this N ‐crotylaniline cyclized considerably more slowly than the corresponding N ‐allylaniline studied under the same conditions previously,6 but N ‐allylfurylamines might be quite sensitive to steric effects in the dienophile part of the molecule 4b . N ‐Allylamines are normally believed to be stable under acidic conditions and show good tolerance of, for instance, acid‐mediated reduction of nitro groups,15 hydrolysis of amides,16 and deformylations,17 but loss of allylic moieties from N ‐allylnaphthylamines was reported as a side reaction when aza‐Claisen rearrangements at elevated temperatures were attempted 18.…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations
“…No formation of alcohol 4b or ketone 5b was observed. It is worth noting that this N ‐crotylaniline cyclized considerably more slowly than the corresponding N ‐allylaniline studied under the same conditions previously,6 but N ‐allylfurylamines might be quite sensitive to steric effects in the dienophile part of the molecule 4b . N ‐Allylamines are normally believed to be stable under acidic conditions and show good tolerance of, for instance, acid‐mediated reduction of nitro groups,15 hydrolysis of amides,16 and deformylations,17 but loss of allylic moieties from N ‐allylnaphthylamines was reported as a side reaction when aza‐Claisen rearrangements at elevated temperatures were attempted 18.…”
Section: Resultsmentioning
confidence: 51%
“…We have previously shown that the presence of electron‐withdrawing substituents ortho and para to the allylamino group increases the reactivity in IMDAF cycloaddition 5. The anilines 1 5,6 were N ‐alkylated with crotyl bromide to give the IMDAF substrates 2 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yan zincir kısmında (tether de) N-KG ve O içeren furan çekirdekli bileşiklerin organik kimyada oldukça zor olan trisiklik ve tetrasiklik fused halkalaşma ürünleri tek adımda Termal ve mikrodalga yöntemle intramoleküler [4+2] Diels-Alder reaksiyonları sonucu elde edilebilmektedir [3,4].…”
Section: Introductionunclassified